AN ANALYSIS OF A TEACHER’S STRATEGIES IN TEACHING ENGLISH READING TO GRADE EIGHT STUDENTS OF SMPN 10 KUPANG IN THE ACADEMIC YEAR 2022/2023 - Meja, Paulina Yuliati Roberta; Feliks, Tans (Postgraduate School, Universitas Nusa Cendana, 2024)
ABSTRACT: The title of this research is An Analysis of a Teacher’s Strategies in Teaching English Reading to Grade Eight Students of SMPN 10 Kupang in the Academic Year 2022/2023. The problems of this study are: (1) What are a teacher’s strategies in teaching English reading to the grade 8 students of SMPN 10 Kupang? (2) What are the problems faced by the teacher in teaching English reading to the grade 8 students of SMPN 10 Kupang? (3) How is the English reading ability of the students when they are taught using those strategies?. This study aims are: (1) to describe a teacher’s strategies in teaching English reading to the grade 8 students of SMPN 10 Kupang; (2) to describe the problems faced by the teacher in teaching English reading to the grade 8 students of SMPN 10 Kupang; and (3) to describe the English reading ability of the students when they are taught using those strategies. The method used in this research was the qualitative method, this research was carried out at grade eight students’ of SMPN 10 Kupang from 24th October until 4th November 2024 and the data were taken through interviews and observation. The findings of this study show that there are four strategies in teaching English reading: memorizing strategy, question-and-answer relationship strategy, game strategy, and discussion strategy. The problems faced in teaching English reading were; limited learning time, students’ various competencies, and students poor vocabulary. The English reading ability of the students when they are taught using those strategies is generally good based on post test score and pre test score.